ERODIBILITAS TANAH DI KECAMATAN PATUK DAN GEDANGSARI, GUNUNGKIDUL - , SURYANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research determines factors affecting the erodibility and distribution rate of the erodibility. This research was soil survey method, conducted at Patuk and Gedangsari area, Gunungkidul in September to December 2013. The results showed that soil erodibility classes in Patuk and Gedangsari consisted of low index covering 989 hectares (14,02%), medium index covering 5.300 hectares (75,16%), medium to high index covering 710 hectares (10,07%), and high index covering 53 hectares (0,75 %). The erodibility factors were organic matter, soil permeability and soil texture. To reduce soil erodibility by increased soil organic matter, and terracing. Key words: erodibility, organic matter, permeability, structure, texture